2020
DOI: 10.5606/ehc.2020.71298
|View full text |Cite
|
Sign up to set email alerts
|

Distal oblique metatarsal osteotomy technique in hallux valgus deformity: Clinical and radiological results

Abstract: This study aims to evaluate the radiological and functional outcomes of hallux valgus patients treated with distal oblique metatarsal osteotomy technique. Patients and methods: Twenty-six feet of 22 patients (4 males, 18 females; mean age 46.2±18 years; range, 16 to 70 years) who were diagnosed as hallux valgus between March 2013 and April 2016 and who underwent distal oblique metatarsal osteotomy were included in this retrospective study. American Orthopedic Foot and Ankle Society/Hallux Metatarsophalangeal-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We found pre-post improvements in the VAS, AOFAS (total score and speci c domains), MOXFQ (total score and speci c domains), PCS and MCS of SF-12, and EQ-5D scores, similar to ndings reported in previous studies. 55,56,57 Although most studies only reported data from the AOFAS and VAS scales, the use of PROMs 58 is encouraged to assess HV surgery outcomes. 59 Their inclusion could provide valuable information for the evaluation of patients' outcomes, 33 and could play an important role in determining the impact of HV surgery on HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…We found pre-post improvements in the VAS, AOFAS (total score and speci c domains), MOXFQ (total score and speci c domains), PCS and MCS of SF-12, and EQ-5D scores, similar to ndings reported in previous studies. 55,56,57 Although most studies only reported data from the AOFAS and VAS scales, the use of PROMs 58 is encouraged to assess HV surgery outcomes. 59 Their inclusion could provide valuable information for the evaluation of patients' outcomes, 33 and could play an important role in determining the impact of HV surgery on HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Following treatment of hallux valgus, Christopher G. Lenz and his colleagues [14] reassessed the post-operative metatarsal cascade and came to the conclusion that the first metatarsal had significantly shrunk. Furthermore, according to Ahmet Kaptanetalstudy [22]'s the first metatarsal length drastically decreased from preoperative measurements. Finally, our study shows that surgical correction of hallux valgus using a scarf and akin osteotomies significantly improves radiological measures.…”
Section: Discussionmentioning
confidence: 96%